Comparative Study on The Contribution Payment System in BPJS With A Tax System-Based Regulation In NHS - Made Cinthya Puspita Shara (Sociological Jurisprudence Journal, 2021)
The purpose of this paper is to examine the efficiencies of United Kingdom life insurance, which is regulated in the NHS with a tax-based funding system. The effectiveness of the Health Insurance System, will provide better health services for the people. Currently, there are still many complaints in the BPJS service system, such as late payments for hospitals and salaries for medical personnel. This study will use the comparative law method, by comparing the BPJS system in Indonesia with the NHS health insurance system in the UK. BPJS uses a monthly fee funding system, the amount of payment are depends on the types of class that BPJS participants has taken. Whereas the NHS only uses a tax-based funding system, where the use of this system can effectively meet all health service needs maximally. Based on the results of research on OECD countries, it is revealed that the tax-based social health insurance program tends to be more progressive and fair. Based on this comparative study, it is important for Indonesia to improve its health insurance system arrangements in order to adapt the tax-based funding system.